The Prognostic Value of Plasma Cell-Free DNA Concentration in the Prostate Cancer: A Systematic Review and Meta-Analysis - Liu, Hongtao; Gao, Yuzhen; Vafaei, Somayeh; Gu, Xiao; Zhong, Xiaoli (Frontiers in Oncology, 2021)
Objective: By virtue of largely disparate clinical outcomes of prostate cancer ( PCA), there is a pressing need to search for useful biomarkers for PCA prognosis. Cell-free DNA (cfDNA) is a promising biomarker for detecting, monitoring, and predicting survival of the prostate cancer (PCA). However, the utility of total cfDNA quantitation in PCA in clinical setting remains elusive. Here, we performed a thorough meta-analysis to assess the prognostic value of cfDNA concentration for patients with PCA. In addition, we tested the possibility of the combination of PSA and cf DNA test results to improve the prediction power in PCA prognosis. Method and materials: More than six databases, including PubMed, Web of Science, Medline, PMC,EMBASE and the Cochrane Library, were searched. Results yielded all eligible articles from the date of inception to June 30, 2020. Continuous, diagnostic and prognostic variables in cfDNA in PCA were includeded in the meta-analyzed by STATA. Results: A total of 23 articles were enrolled in our meta-analysis: 69.6% (16/23)were related to diagnosis, and 56.5%(13/23)were related to prognosis. The pooled concentration of cfDNA in PCA patients was significantly higher than in the control group (SMD=0.89, 95%CI=0.53, 1.26), mirroring results for the prostate-specific antigen (PSA). For the detection test variables, the SROC with 95%CI was 0.87 (0.84-0.90) for cfDNA concentration. In terms of prognostic variables, the concentration of cfDNA were significantly related with progression-free survival (PFS,logHR=0.84(95%CI0.39,1.28)and over all survival (OS,log HR=0.60(95%CI0.29,0.90)).Lastly, the test showed no significant publication bias in the present meta-analysis, excluding the diagnostic meta-analysis. Conclusions: The concentration of Cell-free DNA is high in the prostate cancer patients. The present study substantiates the prognostic value of the cfDNA concentration. High concentration cfDNA correlates with poor disease outcome of CRPC.The study cohort with large sample size is needed to evaluate the prognosis value of cf DNA in the future. We also emphasized that combination of PSA and cf DNA quantitation are important in the future large individual meta study